1994
DOI: 10.1007/bf02574013
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in the numbers of vertices of cubical polytopes, I

Abstract: A cubical polytope is a convex polytope of which very facet is a combinatorial cube. We ask for the numbers which occur as vertex numbers of d-dimensional cubical polytopes, and we show, as a first step, that every cubical d-polytope for even d > 4 has an even number of vertices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Some torsion linear conditions have appeared among the linear conditions for f-vectors of certain cubical complexes [1,2,7]. However, the complete answer is not yet known for these complexes, whereas in our 2-strata case we have a complete answer.…”
Section: Introductionmentioning
confidence: 58%
“…Some torsion linear conditions have appeared among the linear conditions for f-vectors of certain cubical complexes [1,2,7]. However, the complete answer is not yet known for these complexes, whereas in our 2-strata case we have a complete answer.…”
Section: Introductionmentioning
confidence: 58%
“…Let i := y − k − 2 and j := y(y−3) (6) it follows that y ≥ 0 and from (7) it follows that k ≥ 0 if i ≥ 2. If i = 1 and j = 0, then (y, k) = (3, 0).…”
Section: Edge and Ridge Numbers Of 4-polytopesmentioning
confidence: 99%
“…(viii) The possible vertex numbers of cubical 3-polytopes are Π 0 (F 3 cub ) = {8} ∪ {n ∈ Z : n ≥ 10}.Blind & Blind[7] proved that the number of vertices f 0 as well as of edges f 1 are even for every cubical d-polytope if d ≥ 4 is even. According toBlind & Blind [8, Cor.…”
mentioning
confidence: 99%
“…We deal with topological cubical complexes ~ in ~d having additional properties, namely: Such a topological cubical complex is called a special topological cubical (d -t)complex or (d -1)-STC-complex. Clearly, the boundary complex of a cubical d-polytope with fewer than 2 d § 1 vertices is a (d -1)-STC-complex ( (6) is Lemma 3.5, and (7) is satisfied for every cubical polytope, see [3]).…”
Section: Topological Cubical Complexes and Stc-complexesmentioning
confidence: 99%
“…For cubical polytopes it is known that fj(P) > fy(C), where C is a combinatorial cube [2]. In [3] it is shown that fo(P) is even for all even d > 4, and it is reasonable to expect that more gaps occur, especially for numbers slightly larger than fo(C) = 2 d. We determine here all the gaps up to 2 a § that is, we determine all the possible fo(P) up to 2 d+l. However, we do much more.…”
Section: Introductionmentioning
confidence: 99%